Fabrication of GaN nanowires containing n+-doped top layer by wet processes using electrodeless photo-assisted electrochemical etching and alkaline solution treatment. (29th October 2021) - Shimauchi, Michihito; Miwa, Kazuki; Toguchi, Masachika; Sato, Taketomo; Motohisa, Junichi
Abstract: We attempted to fabricate GaN nanowires by electrodeless photo-assisted electrochemical (PEC) etching and successive alkaline solution treatment. The sample consisting of n + -doped and unintentionally doped GaN grown on a GaN substrate was selectively etched using a Ti mask in a mixed solution of K2 S2 O8 and KOH under UV light radiation. This specific layer structure required a relatively concentrated KOH solution for etching. The PEC etching resulted in the formation of a tapered cone structure of GaN with its top diameter determined by the mask size. Successive KOH treatment after PEC etching yielded GaN nanowires with diameters of about 220 nm.